Peningkatan Kedisiplinan dan Hasil Belajar Matematika melalui Metode Reward and Punishment pada Siswa Sekolah Dasar - Pratiwi, Sabilla; Wibowo, Yunus Aris; Rahayu, Widyaningrum Yudi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
Based on initial observations, it was found that there was a problem in the form of low discipline and student learning outcomes, and reward and punishment had not been implemented yet. The study was conducted with the aim of improving discipline and student learning outcomes in mathematics, focusing on the subject of time for 1st grade students at SD Muahmamdiyah 22 Sruni Surakarta, with a total of 18 students. The activities were carried out in 2 cycles, consisting of planning, action, observation, and reflection stages. Data acquisition techniques included observation and written tests. Data were analyzed qualitatively and quantitatively. It was found that discipline improved overall, with a percentage of 46.7% in the pre-cycle, increasing to 71.1% in cycle 1, and further increasing to 87.8% in cycle 2. Meanwhile, student learning outcomes showed an improvement, with a mastery rate of 33.3% and an average score of 58.9 in the pre-cycle, increasing to 55.6% and an average score of 65 in cycle 1, and further increasing to 83.3% with an average score of 86.7 in cycle 2. The data obtained indicate that the implementation of reward and punishment can improve both discipline and student learning outcomes in mathematics.